Improved biodegradation and thermal properties of poly(lactic acid)/layered silicate nanocomposites - Panigrahi M.; Singh N.K.; Gautam R.K.; Banik R.M.; Maiti P. (My University, 2025)
Poly(lactic acid) (PLA)/layered silicate nanocomposites have successfully been prepared using the solution route. Two types of organically modified nanoclays, namely, MEE and MAE have been used. The nanostructure, as observed from wide angle X-ray diffraction, indicates an intercalated hybrid for both PLA-MEE and PLA-MAE, and depends on the type of organic modifier used. Intercalation is higher in PLA-MEE as compared to PLA-MAE system. Crystallite dimensions of nanoclays and nanocomposites have been calculated from the Scherrer equation. Crystallite size of nanocomposites is higher than that of pure nanoclay, which in turn affects the properties of the nanocomposites. Wide angle X-ray diffraction patterns also suggest that PLA and its nanocomposites are predominantly amorphous before annealing but, after annealing, PLA and its nanocomposites are fairly crystalline. The crystallinity of the nanocomposites has decreased in comparison to neat polymer suggesting some sort of interaction between organically modified nanoclay and polymer. The nanohybrids show significant improvement in the thermal properties of the matrix as compared to pristine polymer. The nature of interaction between nanoparticles and polymer is higher in PLA-MEE against PLA-MAE, as evident from the lower value of the heat of fusion in the case of PLA-MEE. The nanoparticles act as nucleating agent, and thereby, control the spherulite dimension of the matrix. The comparison of biodegradation of PLA and its nanocomposites has been studied in several media. Biodegradability of PLA has significantly been enhanced in the presence of nanoclays which has been explained on the basis of amorphous content in the polymer matrix. Finally, the regulated biodegradation has been discussed. © 2010 Koninklijke Brill NV, Leiden.